The Relationship Of The Use Of Female Cleansing Liquid And Pantyliners To The Causes Of Whitening The Pathophys Of Adolescent Women In Hamlet Ii, Bakaran Batu Village, Batang Kuis District, Deli Serdang Regency - Erin Padilla (Institute of Computer Science (IOCS), 2022)
Vaginal discharge is discharge other than blood from the vaginal canal out of the ordinary, either smelly or not accompanied by local itching. According to WHO (World Health Organization) Almost all women and adolescents have experienced vaginal discharge, 60% in adolescents (15-22 years) and 40% in women (23-45 years). And as much as, 75% of Indonesian women must experience vaginal discharge at least 1 time in their life. The purpose of this study was to determine the relationship between the use of feminine hygiene fluids and pantyliners on the causes of pathological vaginal discharge in adolescent girls in Dusun II, Bakaran Batu Village, Batang kuis District. The relationship between the use of feminine hygiene fluids and pantyliners on the causes of pathological vaginal discharge in adolescent girls in Dusun II. This research was conducted from February to June with a population of 68 and a sample of all respondents and sampling using total sampling with the research instrument, namely the questionnaire. Management of data by editing, coding, tabulating, and data entry research results the majority of pathological vaginal discharge 26 respondents (65.0%) used chemical-based feminine hygiene fluids, the majority 31 (77.5%) used pantyliners which used the majority 27 (67.5) %), the study of the relationship between the use of feminine hygiene fluids to the cause of pathological vaginal discharge was obtained (OR) = 5,750% CI = 1,158-28,551 and P. value 0,044 < 0,05, the relationship between the use of pantyliners was obtained (OR) = 0,090% CI = 0,010-0,790 and P. value 0.015 < 0.05, indicating that there is a significant relationship between the use of feminine hygiene fluids and pantyliners on the causes of pathological vaginal discharge. Young women are expected not to use feminine hygiene fluids and pantyliners because they can interfere with vaginal pH, making the vagina moist, which will lead to vaginal discharge.